GAMBARAN PEMENUHAN KEBUTUHAN SEKSUAL WARGA BINAAN LAKI-LAKI DI LEMBAGA PEMASYARAKATAN KLAS IIA YOGYAKARTA - , IPANG FITRIA WANTI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: According to Maslow (1970), there are five basic human needs in a pyramid-like form in accordance with need levels called as Maslowâs hierarchy. The Maslowâs hierarchy is ordered from the bottom to the top of pyramid, from physiological, safety, love, belongingness and love, esteem, and self-actualization needs. In the hierarchy, basic human needs with the highest level are located at the bottom of pyramid, and those with the lowest one is located at the top of pyramid. The meeting of sexual need is included into the physiological needs located at the bottom of Maslowâs pyramid. It shows that according to Maslow, sexual need is very important in human life, so if the need is not met, various sexual deviations will occur. Therefore, however, at anytime, and no matter where, although in the limited moving space for activities such among those undergoing punishment in the prison, the sexual need must be met. Objective: To find out a description of the meeting of sexual need among male inmates in the Prison of Class IIA, Yogyakarta. Method: This study was conducted by a descriptive approach with a quantitative method. The data were analyzed by a univariate descriptive analysis. Samples of the study were 77 female inmates selected using a purposive sampling technique. The inclusion criteria of the study were: (1) the male inmates were in the Prison of Class IIA for more than a year or had undergone a half of punishment duration